Stability and Change in Implicit Bias. (June 2019) - Vuletich, Heidi A.; Payne, B. Keith
Can implicit bias be changed? In a recent longitudinal study, Lai and colleagues (2016, Study 2) compared nine interventions intended to reduce racial bias across 18 university campuses. Although all interventions changed participants' bias on an immediate test, none were effective after a delay. This study has been interpreted as strong evidence that implicit biases are difficult to change. We revisited Lai et al.'s study to test whether the stability observed reflected persistent individual attitudes or stable environments. Our reanalysis ( N = 4, 842) indicates that individual biases did not return to preexisting levels. Instead, campus means returned to preexisting campus means, whereas individual scores fluctuated mostly randomly. Campus means were predicted by markers of structural inequality. Our results are consistent with the theory that implicit bias reflects biases in the environment rather than individual dispositions. This conclusion is nearly the opposite of the original interpretation: Although social environments are stable, individual implicit biases are ephemeral.